Analysis of Product Placement in Web Series and Its Influence on Consumer Buying Behavior (Global Journal of Management and Business Research, 2019)
Web series runs on multiple digital platforms. When it comes to taboo-breaking and intellectual video content, web series have been playing a significant role in India. In a country, where television shows and the different movie or entertainment industries have to face the tight censorship in their content, web series have been the go-to source of thought-provoking entertainment for millennials. Brands are rapidly catching up with this changing trend and started merging their products with the help of product placement in entertainment media. This research is conducted to know whether consumers are affected by product placement or not. Through this paper, we will explore the relationship between product placements and the digital platform.
Keywords: advertising; digital platform; product placement; push or pull marketing; web series